Pengaruh Brand Awareness Dan Brand Trust Terhadap Keputusan Pembelian Pada Produk Revlon - Mutya Afisa; Muhajirin Muhajirin (Journal of Student Research, 2024)
This study aims to determine and analyze the effect of brand awareness and brand trust on purchasing decisions for Revlon products. This type of associative research with primary data and sourced from research instruments in the form of a questionnaire with a Likert scale so that the type of data used is quantitative data. The research population is all consumers who have purchased Revlon products whose number is not known with certainty. The sample of this research was 96 respondents using purposive sampling technique. Data were collected by observation, questionnaires and literature study. Data analysis techniques using validity test, reliability test, classic assumption test multiple regression, multiple correlation coefficient, t test and f test. The results of the study show that band awareness and brand trust have a simultaneous effect on purchasing decisions for Revlon products.